Enhanced laser-energy coupling to dense plasmas driven by recirculating electron currents. (28th March 2018) - Gray, R J; Wilson, R; King, M; Williamson, S D R; Dance, R J; Armstrong, C; Brabetz, C; Wagner, F; Zielbauer, B; Bagnoud, V; Neely, D; McKenna, P
Abstract: The absorption of laser energy and dynamics of energetic electrons in dense plasma is fundamental to a range of intense laser-driven particle and radiation generation mechanisms. We measure the total reflected and scattered laser energy as a function of intensity, distinguishing between the influence of pulse energy and focal spot size on total energy absorption, in the interaction with thin foils. We confirm a previously published scaling of absorption with intensity by variation of laser pulse energy, but find a slower scaling when changing the focal spot size. 2D particle-in-cell simulations show that the measured differences arise due to energetic electrons recirculating within the target and undergoing multiple interactions with the laser pulse, which enhances absorption in the case of large focal spots. This effect is also shown to be dependent on the laser pulse duration, the target thickness and the electron beam divergence. The parameter space over which this absorption enhancement occurs is explored via an analytical model. The results impact our understanding of the fundamental physics of laser energy absorption in solids and thus the development of particle and radiation sources driven by intense laser–solid interactions.